THE USE OF ARTIFICIAL INTELLIGENCE IN EDUCATION - Quronboyeva Dinora Farxod qizi; Anarkulova Zubayda Fayzullo qizi (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article explores the integration and use of Artificial Intelligence (AI) in education, focusing on its potential to transform teaching and learning processes. The study examines the key applications of AI, such as personalized learning, intelligent tutoring systems (ITS), and automated assessments, and highlights their benefits in enhancing student engagement, improving educational outcomes, and supporting teachers. The article also addresses the challenges and ethical considerations associated with AI in education, including data privacy, bias in algorithms, and the role of human educators. The findings suggest that while AI holds great promise for revolutionizing education, its implementation must be carefully managed to ensure equity, fairness, and data security. The article concludes by emphasizing the need for a balanced approach that combines AI technology with human teaching to create an optimal learning environment.